2020
DOI: 10.32598/biomechanics.5.3.3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an 8-week NASM Corrective Exercise Program on Upper Crossed Syndrome

Abstract: Objective Upper Crossed Syndrome (UCS) is a disorder caused by muscle imbalance of the upper quadrant of the body. Using National Academy of Sports Medicine (NASM) protocol for corrective exercises is one of the new approaches to restore muscle balance, and prevent/correct postural abnormalities. The purpose of the present study is to evaluate the effect of an 8-week NASM corrective exercise program on UCS. Methods Participants were 30 female students with forward head > 46 degrees, forward shoulder > 52 degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 27 publications
3
16
0
Order By: Relevance
“…The obtained data indicated that 8 weeks of NASM exercises significantly decreased the angle of HKP and FHP, i.e., consistent with the results obtained by Abdolahzadeh et al [26] and Roshani et al [27]; they evaluated the effects of NASM exercises on individuals with the upper cross syndrome. Conventional corrective exercises focus on stretching shortened muscles and strengthening the weakened muscles.…”
Section: Discussionsupporting
confidence: 90%
“…The obtained data indicated that 8 weeks of NASM exercises significantly decreased the angle of HKP and FHP, i.e., consistent with the results obtained by Abdolahzadeh et al [26] and Roshani et al [27]; they evaluated the effects of NASM exercises on individuals with the upper cross syndrome. Conventional corrective exercises focus on stretching shortened muscles and strengthening the weakened muscles.…”
Section: Discussionsupporting
confidence: 90%
“…Twenty- two eligible studies have investigated the impact of therapeutic exercise on forward head posture [ 5 , 10 13 , 17 , 18 , 22 – 36 ]. Of these studies, three studies had two independent intervention groups that were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies have examined the impact of therapeutic exercise on rounded shoulders [ 5 , 10 13 , 17 , 18 , 22 – 28 , 30 35 ]. Two of these studies had two independent intervention groups, while one study had three independent intervention groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the assessment of the baseline characterization, the participants were assigned to the study groups and randomized allocation sequence by computation. The exercise group participated in the training program for 8 weeks, as followed by the previous studies [28][29][30].…”
Section: Randomization and Blindingmentioning
confidence: 99%